The Relative Weight of Temporal Envelope Cues in Different Frequency Regions for Mandarin Sentence Recognition - Yang Guo; Yuanyuan Sun; Yanmei Feng; Yujun Zhang; Shankai Yin (Neural Plasticity)
Acoustic temporal envelope (E) cues containing speech information are distributed across the frequency spectrum. To investigate the relative weight of E cues in different frequency regions for Mandarin sentence recognition, E information was extracted from 30 contiguous bands across the range of 80–7,562 Hz using Hilbert decomposition and then allocated to five frequency regions. Recognition scores were obtained with acoustic E cues from 1 or 2 random regions from 40 normal-hearing listeners. While the recognition scores ranged from 8.2% to 16.3% when E information from only one region was available, the scores ranged from 57.9% to 87.7% when E information from two frequency regions was presented, suggesting a synergistic effect among the temporal E cues in different frequency regions. Next, the relative contributions of the E information from the five frequency regions to sentence perception were computed using a least-squares approach. The results demonstrated that, for Mandarin Chinese, a tonal language, the temporal E cues of Frequency Region 1 (80–502 Hz) and Region 3 (1,022–1,913 Hz) contributed more to the intelligence of sentence recognition than other regions, particularly the region of 80–502 Hz, which contained fundamental frequency (F0) information.